Influence of salinity on the germination of Iranian alfalfa ecotypes - Torabi, Masoud; Abd Halim, Mohd Ridzwan; Sinniah, Uma Rani; Choukan, R. (Academic Journals, 2011)
Nineteen ecotypes of alfalfa (Medicago sativa) from Iran were evaluated for their salt tolerance based onresponses of their seed germination with increasing salinity levels. Seeds of alfalfa were obtained fromvarious parts of Iran under diverse climatic zones. The study was conducted at Putra MalaysiaUniversity during March 2008. Seeds were placed in petri dishes on filter papers immersed in solutionswith six levels of salinity (0, 50, 100, 150, 200 and 250 mM) using sodium chloride as the salt. Data onseed germination performance were observed over a period of 20 days. Results showed that there weresignificant effects of salinity levels, ecotypes, and interaction between salinity and ecotype ongermination percentage, germination rate and germination index. Reactions of ecotypes to salinitylevels relative to all germination parameter were variable so that there are wide ranges of salt tolerancebetween the ecotypes. Ecotypes originating from the arid and cold areas were more tolerant than otherareas.